2015
DOI: 10.1039/c5ra06762f
|View full text |Cite
|
Sign up to set email alerts
|

Simple green synthesis of solid polymeric bisphenol A bis(diphenyl phosphate) and its flame retardancy in epoxy resins

Abstract: A simple and green method for the preparation of solid polymeric bisphenol A bis(diphenyl phosphate) (PBDP), aimed at improving the flame retardancy of epoxy resins (EP) is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…The absorption peak around 1208 cm −1 was attributed to the CO stretching band. Other absorptions were characteristic of the CH stretching band of the benzene rings (3026 cm −1 ) and the CC stretching band in the benzene ring (1599 and 1509 cm −1 ) . The characterization results of FTIR spectroscopy and NMR confirmed that ADDPP‐OH was synthesized successfully.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…The absorption peak around 1208 cm −1 was attributed to the CO stretching band. Other absorptions were characteristic of the CH stretching band of the benzene rings (3026 cm −1 ) and the CC stretching band in the benzene ring (1599 and 1509 cm −1 ) . The characterization results of FTIR spectroscopy and NMR confirmed that ADDPP‐OH was synthesized successfully.…”
Section: Resultsmentioning
confidence: 77%
“…Other absorptions were characteristic of the CAH stretching band of the benzene rings (3026 cm 21 ) . 25,26 The characterization results of FTIR spectroscopy and NMR confirmed that ADDPP-OH was synthesized successfully.…”
Section: Structural Characterizationmentioning
confidence: 79%
“…EP normally releases massive heat and smoke during combustion, which greatly limits its further applications. Therefore, the study on flame retarded EP has become a hot field in recent years . Among the flame retardant EP system, halogen‐containing flame retardant has the highest efficiency, but results in environmental issues during combustion .…”
Section: Introductionmentioning
confidence: 99%
“…and Denchev et al 2009, Perret, Schartel et al et al 2011, Zang, Wagner et al et al 2011, Liang, Cao et al et al 2013, Ménard, Negrell et al et al 2015, Xu, Zhao et al et al 2015, Zhao, Liu et al et al 2015 DOPO-based curatives, as shown in Scheme 1-26, were reported to cure o-cresol formaldehyde novolac epoxy and DGEBA. (Cho, Fu et al et al 1998, Wang and Lin et al 1999, Nakamura, Asano et al et al 2003) DGEBA cured with the DOPO-based amide compound shown in Scheme 1-26 had a 32% char residue at 700 o C under N 2 and the LOI value was 30 % (Wang and Lin et al 1999).…”
Section: Os3mentioning
confidence: 99%
“…(PBDP, Scheme 1-22) showed a flame-retardant mechanism in both the gas and condensed phases in a DGEBA-(m-PDA) system. (Zhao, Liu et al et al 2015) A 20 wt% loading of PBDP was needed to achieve a UL 94 V-0 rating for this system. In a DEN 438-DICY/fenurone system, an 11.5 wt% PBDP loading (2 wt% P loading in epoxy) was needed to achieve a V-0 rating.…”
Section: Scheme 1-13 Structures Of Pdms and Possmentioning
confidence: 99%